Representing Baby Blues Syndrome on @mubadalah.id: A Multimodal and Intersectional Analysis - Erni Dewi Riyanti; Suhandano Suhandano; Hendrokumoro Hendrokumoro (Sawwa: Jurnal Studi Gender, 2026)
Women undergo significant identity changes during the transition to motherhood, which is often culturally viewed as the pinnacle of a woman’s achievements. This study examines the perspectives presented on the Instagram account @mubadalah.id regarding motherhood, mental health, and Baby Blues Syndrome (BBS) using Machin and Mayr’s multimodal content analysis and Crenshaw’s intersectional feminism. The results of the analysis show that the text positions women as the primary actors through word choice, overlexicalization, and structural opposition that highlight the causes and experiences of BBS. Visual analysis reveals a dominance of representations of domestic spaces associated with motherhood. The intersectional approach reveals that BBS is related to identity transitions, parental responsibilities, and various forms of multidimensional oppression. Support from fellow mothers is presented as an inclusive solution. Nevertheless, the representation of the challenges of motherhood remains limited to the domestic sphere. This study contributes to research on language, media, and maternal mental health, while also enriching the understanding of the Islamic perspective on this issue.